PENINGKATAN KETERAMPILAN MEMBACA PUISI DENGAN MENGGUNAKAN TEKNIK PEMODELAN PADA SISWA KELAS III SD NEGERI MENDUNGAN 1 KOTA YOGYAKARTA - Fetri Kusumawati; Siti Rochmiyati (Universitas Sarjanawiyata Tamansiswa, 2016)
This study aimed to describe the increase in activity and the skills of reading poetry in the third grade students of State Elementary School Mendungan 1 Yogyakarta using modeling techniques. This research is a classroom action research collaborative. Subjects of this study 21 students. The object of this research activity and the value of poetry reading skills. This research was conducted in two cycles. Instruments using observation, testing, and documentation. Test the validity of the data using content validity and interrater reliability. The results showed that the activity of students in prasiklus amounted to 55.6 % in the category enough, the first cycle to 70.4 % in both categories, and the second cycle be 80.8 % in both categories. Skills to read poetry on prasiklus 0 % , 52.4 % in the first cycle, and the second cycle be 85.7 %.